1992
DOI: 10.1128/mcb.12.12.5394
|View full text |Cite
|
Sign up to set email alerts
|

ACR1, a yeast ATF/CREB repressor.

Abstract: Members of the mammalian ATF/CREB family of transcription factors, which are associated with regulation by cyclic AMP and viral oncogenes, bind common DNA sequences (consensus TGACGTCA) via a bZIP domain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
63
1

Year Published

1993
1993
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 58 publications
5
63
1
Order By: Relevance
“…Sko1p Homodimerization in Vivo Is Not Affected by Os- motic Stress-CREB transcription factors bind to their CRE recognition sequences as homo-or heterodimers (11,14). To determine whether dimerization of Sko1p in vivo plays a role in the regulation of this transcriptional repressor by osmotic stress, we assayed for Sko1p-Sko1p interaction by coprecipitation experiments.…”
Section: Deletion Analysis Of Sko1p: a Central Region (315-486) Is Rementioning
confidence: 99%
See 1 more Smart Citation
“…Sko1p Homodimerization in Vivo Is Not Affected by Os- motic Stress-CREB transcription factors bind to their CRE recognition sequences as homo-or heterodimers (11,14). To determine whether dimerization of Sko1p in vivo plays a role in the regulation of this transcriptional repressor by osmotic stress, we assayed for Sko1p-Sko1p interaction by coprecipitation experiments.…”
Section: Deletion Analysis Of Sko1p: a Central Region (315-486) Is Rementioning
confidence: 99%
“…In the yeast Saccharomyces cerevisiae the function of the CREB repressor Sko1p (10,11) has been identified recently. Sko1p represses gene expression from CRE promoter sequences of various osmoinducible genes such as ENA1 (Na ϩ extrusion ATPase) (12), HAL1 (ion homeostasis protein) (13), or GRE2 (homolog to plant isoflavonoid reductase) (14 -16).…”
mentioning
confidence: 99%
“…We previously suggested that AP-1 and ATF/CREB proteins make similar DNA contacts but differ in half-site spacing preferences, and we predicted that the connection between the leucine zipper and basic region (residues 244-250) determines the flexibility and specificity of half-site spacing (13). In this regard, there is a consistent difference at the position corresponding to GCN4 residue 247: ATF/ CREB proteins have a positively charged residue (nearly always lysine), whereas AP-1 proteins do not (GCN4 contains a leucine) (16).…”
mentioning
confidence: 99%
“…Repressors can inhibit transcription of their target genes by inhibiting the functions of activators by simply competing for the binding sites on the promoters (33)(34)(35). Repressors can also inhibit transcription through downregulation of the DNA-binding or transactivation activity of activators by forming complexes with them (36,37).…”
Section: Fig 6 Tpbf Is the Only Protein Responsible For Activation mentioning
confidence: 99%